2013
DOI: 10.1177/0363546513509051
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Ulnar Collateral Ligament Reconstruction Techniques

Abstract: A lower complication rate can lead to increased rates of return to play and better outcomes postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 26 publications
2
99
0
Order By: Relevance
“…12 The most common complication is ulnar nerve neuropraxia, which can be seen in approximately 10% of cases. Different techniques have been described for the approach to the flexor-pronator mass, location of humeral tunnels, choice of graft fixation, and performance of an ulnar nerve transposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 The most common complication is ulnar nerve neuropraxia, which can be seen in approximately 10% of cases. Different techniques have been described for the approach to the flexor-pronator mass, location of humeral tunnels, choice of graft fixation, and performance of an ulnar nerve transposition.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review comparing UCL reconstruction techniques, the docking technique resulted in a significantly higher rate of return to play (90.4% vs 66.7%) and a lower complication rate (6.0% vs 29.2%) when compared with the Jobe and modified Jobe techniques. 12 In a biomechanical comparison of fixation methods, the docking technique had a significantly higher load to failure compared with Jobe and interference screw techniques 13 (Table 2). Our technique has advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…25,27 A curvilinear incision posterior to the medial epicondyle is made, and the medial antebrachial cutaneous branches are protected. The ulnar nerve, which is identified running between the 2 heads of the flexor carpi ulnaris (FCU), is also carefully protected.…”
Section: Surgical Techniquementioning
confidence: 99%
“…While the improved surgical options have, indeed, translated to improved functional and patient outcomes, the treatment algorithm for MUCL tears remains elusive. Hurwit et al surveyed 159 members of the American Shoulder and Elbow Surgeons and reported that professional athletes and those with complete tears were indicated for surgery by consensus; opinion was more divided on how to treat partial tears or non‐professional athletes.…”
Section: Introductionmentioning
confidence: 99%